Minecraft. The sky's the limit! - Eliopulos, Nick; Batson, Alan (New York : Random House, 2023)
Young players Emmy and Birch, along with their tame wolf Byte, embark on an incredible journey to gather the right materials to go flying.
2.2
K-3
580L
Keywords: Minecraft (Game) -- Juvenile fiction; Video games -- Juvenile fiction; Adventure stories; Minecraft (Game) -- Fiction; Video games -- Fiction; Adventure and adventurers -- Fiction; Action and adventure fiction; Readers (Elementary)